Antimicrobial Activity of Copper(II), Nickel(II) and Zinc(II) Complexes with Semicarbazone and Thiosemicarbazone Ligands Derived from Substituted Salicylaldehydes - Alessio Zavaroni; Luca Rigamonti; Franco Bisceglie; Mauro Carcelli; Giorgio Pelosi; Giovanna Angela Gentilomi; Dominga Rogolino; Francesca Bonvicini (Molecules)
Antibiotic resistance is a problem repeatedly reported by health authorities. Metalloantibiotics, i.e., biologically active compounds containing one or more metal ions, can be an important resource in the fight against bacteria and fungi. Here, we report the results obtained with a panel of copper(II), nickel(II) and zinc(II) complexes with thiosemicarbazone, semicarbazone and acylhydrazone ligands on Staphylococcus aureus, Escherichia coli and Candida albicans, taken as model systems of human pathogens. To increase the solubility in water, the sulfonic group was introduced on some of the ligands, isolating them as sodium salts (NaH2L4-NaH2L7). Complexes 1–14 were isolated, fully characterized and the X-ray structures of 11, 12 and 13 were obtained. While all the ligands have no antimicrobial activity, the copper(II) complexes 1 and 4 and the nickel(II) complex 2, obtained from thiosemicarbazone ligands, showed good activity, in particular against S. aureus; these complexes were investigated in depth, calculating their respective IC50 values (4.2 μM, 3.5 μM and 61.8 μM, respectively). It should be noted that nickel(II) complex 2 does not show hemolytic activity and has a favorable SI value. While all the copper(II) complexes completely degraded the plasmid DNA in presence of H2O2, nickel(II) complex 2 cleaved the plasmid DNA leading to the formation of the relaxed nicked conformation, thus suggesting a different mechanism of action.